An overview of the coal ash transition process from solid to slag. (1st March 2021) - Shi, Wenju; Bai, Jin; Kong, Lingxue; Li, Huaizhu; Bai, Zongqing; Vassilev, Stanislav V.; Li, Wen
Highlights: Ash fusion process can be characterized by shrinkage and slag transition curves. Ash fusion process passes through two to three stages. B/A and AFT index are good for evaluation of sintering and slagging. The shape of the shrinkage curve can be used to define ash fusion mechanism. Abstract: Coal ash-related issues seriously restricted the industrialization of entrained flow gasification. Although extensive and high-quality studies concerning these issues have been done in the past, numerous problems were still uncertain or incompletely understood about the fusion process in multicomponent coal ash systems. Therefore, this review proceeded the whole ash transition process by the exploration of the shrinkage properties and slag transition of coal ash. The results demonstrated that the ash fusion process passed through two to three stages as the start and end temperatures of each stage were related to either sintering temperature or ash fusion temperatures (AFTs). Besides, indices for the evaluation of sintering and slagging severity were introduced and compared. These indices were classified into three types based on different approaches: (1) empirical index from chemical compositions, (2) index based on depositing mechanisms, (3) index from AFTs. The comparison among these indices showed that the base/acid ratio (B/A) and ash fusion temperature index (AFTI) had good uniformity and they could be regarded as the preferred criteria for sintering and slagging. On the other hand, indices such as Fe2 O3 and Fe2 O3 /CaO could be used to a lesser extent for the above purposes. Subsequently, the ash fusion mechanism was discussed from three aspects, namely, minerals transformation, molecular dynamics simulations and kinetic analysis. More specifically, the transformation of minerals was mainly concentrated on chemical reactions, and the kinetic analysis was obtained from melting transition degrees. Finally, some challenges and prospects related to coal ash fusion and entrained flow gasification technology were discussed.